N,N-dimethylformamide: evidence of carcinogenicity from national representative cohort study in South Korea - Jin-Ha Yoon; Cheol-In Yoo; Yeon-Soon Ahn (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVE: There is limited epidemiological evidence of carcinogenicity on exposure of N,N-dimethylformamide (DMF). This study aimed to identify the possible association between cancer mortality and DMF exposure. METHODS: A cohort of 11 953 workers exposed to DMF between 1 January 2000 and 31 December 2004 was studied. A urinary metabolite of DMF, N-methylformamide level (UNMFL), was used for exposure assessment. This cohort was matched with the mortality data of the Korean National Statistical Office and followed up for cancer mortality between 2000 and 2011. Standardized mortality ratios (SMR) of the DMF-exposed workers with reference to Korean men were calculated. Adjusted hazard ratios (HRadj; also controlling for age, other carcinogen exposure including hepatitis B and C) were calculated for the workers categorized in three exposure groups with reference to workers with no exposure. RESULTS: The HRadj of overall cancer mortality were significantly increased in workers with 7.5-<15 mg/L [HRadj 2.72, 95% confidence interval (CI) 1.09-6.81] and ≥15 mg/L (HRadj 2.41, 95% CI 1.03-5.66) compared with non-exposed workers. Hepatocellular carcinoma mortality (HRadj 3.73, 95% CI 1.05-13.24) of workers with ≥15 mg/L and lung cancer mortality (HRadj 14.36, 95% CI 1.41-146.86) in workers with 7.5-<15 mg/L were significantly increased. CONCLUSIONS: Workers with high DMF exposure showed increased mortalities for overall, liver, and lung cancer. Our results suggest that DMF causes cancer, especially hepatocellular carcinoma, which is in agreement with earlier studies on liver cancer in animal experiments.